Gastric myoelectrical activity abnormalities of electrogastrography in patients with functional dyspepsia - Kayar, Yusuf; Danalıoğlu, Ahmet; Al Kafee, Abdullah; Okkesim, Şükrü; Şentürk, Hakan (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Pathogenesis of functional dyspepsia (FD) is unclear and not well documented. Some gastric motility abnormalities have been reported to be important factors. Transcutaneous electrogastrography (EGG) is an experimental method that is used to assess FD. We aimed to compare FD patients with control subjects in terms of motility abnormalities according to the EGG results. Materials and Methods: Thirty patients with FD and thirty control subjects were included. EGG was preprandially and postprandially performed. The recordings were analyzed and compared between the two groups. Results: Mean ages of the cases and controls were 31.4±9.3 and 32.58±7.6 years, respectively. Female subjects constituted 80% of the FD group and 76.67% of the control group. In terms of the preprandial dominant frequency (DF), the FD group demonstrated lower incidence of normal subjects than the control group [13 (43.3%) and 22 (73.3%), respectively] and a higher incidence of bradygastria than the control group [17 (56.7%) and 8 (26.6%), respectively]. In the FD group, the rate of cases with normal postprandial DF was lower than that in the control group [10 (33.3%) and 23 (76.7%), respectively], whereas the rates of bradygastria [18 (60%) and 7 (23.3%), respectively] and tachygastria [2 (6.7%) and 0 (0%), respectively] were higher in the FD group (p<0.05). Preprandial and postprandial DF values were statistically significant in both groups. Conclusion: A high incidence of gastric motility and myoelectrical activity abnormalities was observed in patients with FD. EGG is an effective, reliable, and non-invasive method in differentiating the subgroups. After standardization of some parameters, EGG may be an essential and irreplaceable test to diagnose and follow-up FD patients with motor dysfunction.